Case Report: Orchiopexy in Two Poodle Dogs and Its Effect on Their Sperm Quality Parameters - Mahiddine, Feriel Yasmine; Kim, Min Jung (Frontiers in Veterinary Science, 2021)
Cryptorchidism is a common congenital abnormality encountered in veterinary clinics. The treatment of choice for this condition is a surgical procedure named orchiectomy or orchidectomy, where the retained testicle is removed. Surgical placement and fixation of the cryptorchid testicle into the scrotum, referred to as orchiopexy, is used in Humans. However, due to the hereditary nature of cryptorchidism in dogs, this treatment option has not been proposed in veterinary clinics. Two adult Poodle dogs were referred to our research facility for a sperm parameter evaluation check. The two dogs were unilateral cryptorchid dogs treated with orchiopexy before the age of 6 months. Their sperm kinematics and morphology were within normal ranges, and their libido and testicles sizes were normal. Treatment of unilateral cryptorchidism by orchiopexy in dogs before the age of 6 months successfully restored spermatogenic function and sperm quality-related parameters. However, due to the nature of this condition, orchiectomy remains the treatment of choice.